Estabilidad en el servicio de traslado de chatarra al patio de preparación para la cesta en Sider- Gerdau, de junio a agosto del 2011 - Alfaro Flores, Felipe (2012)
This experiment was conducted at the Steel Company of Peru (Sider, Gerdau) in metal patio area. For this was the recording process during the months of June to August 2011. The records were organized using the facilities of the Excel spreadsheet for each month, mobile and shift. So it was out of time and study activities in the transfer of raw material (scrap) for mobile equipment (bucket trucks) during the day. The problem was, Does the process of transfer of scrap to the yard in preparation for the basket is stable over the months, shifts and mobile units involved, in terms of numbers of trips per day, while in cycles and weight of cargo carried, for the period June to August 2011?. The Department of Logistics-Transportation, this tube designed to determine the stability of the process of moving the yard junk la cesta preparedness, in terms of numbers of trips per shift, the weight of cargo for each cycle for each phone. The result was that the process is stable